Present situation analysis within critical-complex pedagogy: surfing the text, the context and the discourse - Vieira, Bruna Gabriela Augusto Marçal (Letras, 2022)
This paper discusses the improvements that critical-complex pedagogy proposes to present situation analysis – a fundamental pre-course investigation of students’ communicative and learning needs and wants in English for Specific Purposes literature. The pedagogy expands students’ communicative needs analysis beyond rhetorical and linguistic conventions of the target discourse. A three-phase investigation for the design of an online Critical English for Academic Purposes course is presented and demonstrates the potentialities of the pedagogy to orient the investigation of students’ pre-course knowledge about textual, contextual and discursive features of the target genres, in order to identify their literacy skills to produce those genres.